Kepadatan dan keanekaragaman makrozoobentos pada ekosistem mangrove di perairan pantai Desa Sehati, Kabupaten Maluku Tengah - Melsasail, Karel Markus (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Sehati is a village in Central Maluku Regency which has one of the coastal supporting ecosystems in the form of mangroves with an area of ??66.5 ha. The mangroves produce a large amount of detritus which mainly comes from litter. The detritus is utilized by macrozoobenthos as food, thereby increasing the number of species. However, it is feared that logging by local communities can put significant pressure not only on mangroves but also on macrozoobenthos because they are very sensitive to changes in environmental conditions in which they live.The purpose of this study was to analyze the density and diversity of macrozoobenthos species in the mangrove ecosystem in Sehati Village, Central Maluku Regency.The collection was carried out using a linear quadratic transect method. The transects used were 5 pieces with a square measuring 1x1 meter as many as 10 pieces, and supported by measurements of various physical and chemical parameters of the waters. There are 19 species of macrozoobenthos found in the mangrove ecosystem in the coastal waters of Sehati Village. Nassarius luridus has the highest density value (0.595 ind/m2), while Neries virens has the lowest density value (0.025 ind/m2).The value of the diversity index of macrozoobenthos in the mangrove ecosystem is high (2,631).The condition of the physical and chemical factors of the waters in the mangrove ecosystem is still in good condition for the growth of macrozoobenthos.